Swiping for connection: tribe identity and sexual health among sexual minority men who use dating apps - Mathew, Krupa Ann; Zhao, Yunan; Tran, Alvin (Frontiers in Communication, 2025)
BackgroundDating applications, or “dating apps,” are widely used by sexual minority men (SMM) to form social and sexual connections. These platforms support intimacy, identity expression, and community engagement but have also been linked to sexual health risks and psychological distress. Although research on dating app use is growing, studies remain limited. This study examines dating app use, tribe identity, and sexual health behaviors in a sample of U.S. SMM.MethodsA total of 549 gay and bisexual men aged 18–50 years completed an online survey and were recruited via Qualtrics Survey Panels, assessing dating app use, tribe identity, sexual activity, condom use, and awareness and use of pre-exposure prophylaxis (PrEP). Descriptive statistics explored patterns of digital engagement, identity expression, and sexual health behaviors.ResultsMost participants (69.4%) reported using dating apps, primarily for casual sex (46.3%). Among sexually active participants, 39.9% did not use condoms during their last sexual encounter. Only 17.8% of those aware of PrEP were currently using it, and 33.5% had never heard of it. Tribe identity was diverse but not universal; 32.1% reported no affiliation, while others identified with groups such as “Clean-cut,” “Bear,” and “Jock,” revealing potential links to appearance-based norms and sexual decision-making.ConclusionDating app use may influence both health behaviors and digital communication patterns among sexual minority men. Our findings underscore the need for inclusive, culturally responsive interventions that address gaps in sexual health knowledge while also considering how digital discourse and platform design shape communication, perception, and engagement.